(untitled) (Journal of the College of Basic Education, 2023)
The current research aims to identify (the effect of the FARC model based on learning patterns on the acquisition of grammatical concepts for fifth grade students) and to achieve the two objectives of the research, the researcher put the following hypotheses: There are no statistically significant differences between the average scores of the experimental group students who study according to the FARC model of learning patterns and between The average grades of the control group students who study from: By checking the formulation of the following null hypothe